Identification of Amino Acid Residues in the Caenorhabditis elegans POU Protein UNC-86 That Mediate UNC-86–MEC-3–DNA Ternary Complex Formation - Röckelein, Inge (American Society for Microbiology, 2000)
The POU homeodomain protein UNC-86 and the LIM homeodomain protein MEC-3 are essential for the differentiation of the six mechanoreceptor neurons in the nematode Caenorhabditis elegans. Previous studies have indicated that UNC-86 and MEC-3 bind cooperatively to at least three sites in the mec-3 promoter and synergistically activate transcription. However, the molecular details of the interactions of UNC-86 with MEC-3 and DNA have not been investigated so far. Here we used a yeast system to identify the functional domains in UNC-86 required for transcriptional activation and to characterize the interaction of UNC-86 with MEC-3 in vivo. Our results suggest that transcriptional activation is mediated by the amino terminus of UNC-86, whereas amino acids in the POU domain mediate DNA binding and interaction with MEC-3. By random mutagenesis, we identified mutations that only affect the DNA binding properties of UNC-86, as well as mutations that prevent coactivation by MEC-3. We demonstrated that both the POU-specific domain and the homeodomain of UNC-86, as well as DNA bases adjacent to the proposed UNC-86 binding site, are involved in the formation of a transcriptionally active complex with MEC-3. These data suggest that some residues involved in the contact of UNC-86 with MEC-3 also contribute to the interaction of the functionally nonrelated POU protein Oct-1 with Oca-B, whereas other positions have different roles.